ARE THERE DIFFERENCES IN WILLINGNESS TO PAY AMONG VISITORS AND NON-VISITORS OF TAMAN NEGARA NATIONAL PARK? - Zaiton Samdin; Khairil Wahidin Awang (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
Approaches such as the Contingent Valuation Method (CVM) have helped to assign dollar values to non-use values for non-market goods which, unlike other products, are not traded in the market. This study attempts to put a value on the above non-market values. This study used the CVM, with Willingness to Pay (WTP) as the elicitation method to measure the non-use value among visitors and non-visitors of Taman Negara National Park (TNNP). This study also will answer questions; are there any differences in the WTP of various market segments, based on nationality, gender, age, education and income among visitors and non-visitors? This study found that there was a different between visitors and non-visitors willingness to pay. It also found that visitors and non-visitors market segments such as nationality,, income etc. are differed. Thus, information found in this study can be a fundamental source for park management in directing park pricing policy towards an efficient system. Although using WTP for this economic valuation cannot provide exact answers on the valuation of these natural resources, it can still provide a guideline on pricing strategy and give extra information for park management decisions, especially about park pricing. Thus, better decision-making processes can be practised if monetary values can be placed on these non-market goods.